2018
DOI: 10.1186/s12931-018-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of systemic IL-10 levels with proinflammatory cytokine responsiveness and lung function in agriculture workers

Abstract: BackgroundAgriculture workers are exposed to microbial component- and particulate matter-enriched organic dust aerosols. Whereas it is clear that exposure to these aerosols can lead to lung inflammation, it is not known how inflammatory responses are resolved in some individuals while others develop chronic lung disease. Interleukin (IL)-10 is an immunomodulatory cytokine that is recognized as a potent anti-inflammatory and pro-resolving factor. The objective of this study was to determine whether there is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…In the present study, it was found similar response, since policemen working in a shiftwork scale presented reduced levels of IL‐10 and reduced FEV1. These findings reinforce the findings of previous studies performed in asthmatics, 25 demonstrating a possible association between lower levels of IL‐10 with airway inflammation and airway obstruction. In fact, this concept that low levels of IL‐10 can be associated with airway obstruction is strengthened by the present study, since that such phenomena were also found in non‐asthmatic patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, it was found similar response, since policemen working in a shiftwork scale presented reduced levels of IL‐10 and reduced FEV1. These findings reinforce the findings of previous studies performed in asthmatics, 25 demonstrating a possible association between lower levels of IL‐10 with airway inflammation and airway obstruction. In fact, this concept that low levels of IL‐10 can be associated with airway obstruction is strengthened by the present study, since that such phenomena were also found in non‐asthmatic patients.…”
Section: Discussionsupporting
confidence: 91%
“…On the other side, increased levels of blood IL‐10, an immunomodulatory and anti‐inflammatory cytokine has been associated increased and better FEV1/FVC values, which is also an important marker of airway obstruction 25 . In the present study, it was found similar response, since policemen working in a shiftwork scale presented reduced levels of IL‐10 and reduced FEV1.…”
Section: Discussionsupporting
confidence: 72%
“…In relation to marathons, our group previously demonstrated that marathon runners who had increased IL-10 levels in the circulation immediately after the marathon and also in the nasal mucosa 72 hours after the marathon did not present upper respiratory symptoms [12,33]. In addition, it has been also reported that systemic IL-10 can modulate the pulmonary function by modulating the inflammatory response of the airways [29,45], including that associated with physical exercise [50,51]. However, studies that aimed to evaluate the effect of IL-10 in the context of EIB are scarce [52,53].…”
Section: Discussionmentioning
confidence: 95%
“…Another factor that may influence the similar performance observed between the two groups is the higher circulant IL-10 levels found immediately after the marathon. It is well-known that IL-10 has a potent anti-inflammatory and proresolving properties [45] and, in the airways, can act as a protective factor against mucosal inflammation [46].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the regulatory role and direct action of IL-4 on effector cells in allergic inflammation, this cytokine also appears to have actions relevant to smoking-related diseases. IL-10 is an anti-inflammatory and pro-resolving factor that can work to inhibit pro-inflammatory cytokines [22] . Increased IL-4 is associated with allergic airway response; [23] and both IL-4 and IL-10 alter macrophage lipid metabolism [24] .…”
Section: Discussionmentioning
confidence: 99%